The Role of Social Capital and Knowledge Capital for Freelance Creative Workers in Audiovisual Industry: - - Ramadhiani, Fadhilia Resti; Adnan, Ricardi S. (The Journal of Society and Media, 2023)
This study explains how capitals shape the survival strategy of freelance creative workers who work in a precarious situations in the commercial audiovisual industry. This study was conducted with a qualitative approach. Through in-depth interviews with freelance creative workers, online observations, and digital data collection, this study shows that the survival strategy of the workers can be explained further based on capital analysis focused on social capital and knowledge capital as the recognized and valued capital in the field. Both the social and knowledge capital of the workers, accompanied by workers’ capacity to accumulate and convert them continuously, are relevant in shaping workers’ survival strategy, which leads to the establishment of a positive reputation and capacity enhancement. This eventually leads them to gain employability and occupy strategic positioning, reflected in high bargaining power and work opportunities in the industry sustainably, as it becomes their alternative job security to survive amidst precarious conditions